The impact of ocean biogeochemistry on physics and its consequences for modelling shelf seas. (April 2022) - Skákala, Jozef; Bruggeman, Jorn; Ford, David; Wakelin, Sarah; Akpınar, Anıl; Hull, Tom; Kaiser, Jan; Loveday, Benjamin R.; O'Dea, Enda; Williams, Charlotte A.J.; Ciavatta, Stefano
Abstract: We use modelling and assimilation tools to explore the impact of biogeochemistry on physics in the shelf sea environment, using North-West European Shelf (NWES) as a case study. We demonstrate that such impact is significant: the attenuation of light by biogeochemical substances heats up the upper 20 m of the ocean by up to 1 °C and by a similar margin cools down the ocean within the 20–200 m range of depths. We demonstrate that these changes to sea temperature influence mixing in the upper ocean and feed back into marine biology by influencing the timing of the phytoplankton bloom, as suggested by the critical turbulence hypothesis. We compare different light schemes representing the impact of biogeochemistry on physics, and show that the physics is sensitive to both the spectral resolution of radiances and the represented optically active constituents. We introduce a new development into the research version of the operational model for the NWES, in which we calculate the heat fluxes based on the spectrally resolved attenuation by the simulated biogeochemical tracers, establishing a two-way coupling between biogeochemistry and physics. We demonstrate that in the late spring–summer the two-way coupled model increases heating in the upper oceanic layer compared to the existing model and improves by 1–3 days the timing of the simulated phytoplankton bloom. This improvement is relatively small compared with the existing model bias in bloom timing, but is sufficient to have a visible impact on model skill in the free run. We also validate the skill of the two-way coupling in the context of the weakly coupled physical–biogeochemical assimilation currently used for operational forecasting of the NWES. We show that the change to the skill is negligible for analyses, but it remains to be seen how much it differs for the forecasts. Highlights: For the shelf seas, biogeochemistry has important impact on temperature and mixing. Simulated physics is sensitive to the model light scheme. The two-way coupled physical-biogeochemical model improves the spring bloom timing. We have validated the developments within the operational set-up.